Self Concept and Communication Adaptation Among First Year University Students: Konsep Diri dan Adaptasi Komunikasi di Kalangan Mahasiswa Baru Universitas - Akhmad Kholis; Nurvi Laili (Academia Open, 2025)
General Background Transition into university life requires students to adjust socially and psychologically to new academic and interpersonal environments. Specific Background First year students frequently encounter communication barriers and social difficulties that relate to their personal self concept and confidence in interaction. Knowledge Gap Previous studies have discussed self concept and adjustment separately, yet limited research has examined their relationship within communicative adaptation among new university students. Aims This study aims to analyze the relationship between self concept and communication adaptation ability among first year students. Results Statistical analysis indicates a positive and significant association, showing that students with stronger self perceptions demonstrate better interpersonal adjustment and interaction skills. Novelty The study integrates self concept theory with communicative adaptation measures in a specific freshman context, providing combined psychological and communication perspectives. Implications Findings support the need for guidance programs and campus interventions that develop students’ self awareness and social competence to facilitate smoother academic integration. Keywords: Self Concept, Communication Adaptation, First Year Students, Interpersonal Skills, Student Adjustment Key Findings Highlights: Positive personal perception aligns with smoother social adjustment Freshmen with higher confidence display stronger interaction competence Guidance services recommended to support early campus transition